Integral Valorization of the Invasive Lissachatina fulica in Madagascar : A Zero-Waste Pathway to Nutritional Security and the Green Circular Economy - Odon, Fetisondraibe Zafimamonjy Louis; Daniel, Razafindrazanakolona Andriamanjato; Tahina, Rabeharitsara Andry; Tsaroana, Verofaniry Nomena; Baholy, Robijaona Rahelivololoniaina (Budapest International Research in Exact Sciences (BirEx) Journal, 2025)
Confronting critical imperatives of global food security and environmental sustainability, this investigation delineated the nutritional and mineral composition of the invasive African Giant Snail, Lissachatina fulica, thriving in Madagascar. Using standard biochemical assays and Total Reflection X-ray Fluorescence (TXRF) spectroscopy on a cohort of 30 individuals, the shell, flesh, and mucus were precisely evaluated. The resultant data reveal a compelling paradigm for integral bioresource valorization based on functional complementarity. The flesh exhibits a remarkable protein concentration of 63.58 % on a dry matter (DM) basis and contains substantial levels of essential micronutrients, notably Magnesium (1.57 % DM) and Iron (0.42 % DM). This profile validates the snail as a high-quality, sustainable protein resource capable of significantly fortifying regional food security initiatives. The mucus fraction is notably distinguished by its richness in protein (74.13 % DM) and Silicon (1.27 %), emphatically corroborating its high potential for therapeutic and cosmetic dermatological applications. The shell, overwhelmingly calcareous, boasts an elevated calcium concentration of 18.15 %, positioning it as a compelling source for nutritional supplements or advanced biomaterials. Crucially, the rigorous chemical analysis established the absence of detectable levels of toxic heavy metals (Pb, Cd, As, Hg) across all fractions, incontrovertibly affirming the safety and innocuousness of these derived materials. This study decisively substantiates the potential for harnessing a problematic invasive organism as a key green bioresource, validating the deployment of a holistic, "zero-waste" circular economy approach contributing synergistically to both nutritional security and sustainable economic development in Madagascar.